Voltage Setup Problem for Embedded Systems With Multiple Voltages. - Hua, S. (IEEE Transactions on VLSI systems)
We formulate the following voltage setup problem: how many levels and at which values should voltages be implemented on the system to achieve the maximum energy saving by dynamic voltage scaling (DVS)? This problem challenges whether DVS technique's full potential in energy saving can be reached on multiple voltage systems. In this paper, 1) we derive analytical solutions for dual-voltage system; 2) we develop efficient numerical methods for the general case where analytical solutions do not exist; 3) we demonstrate how to apply our proposed algorithms in system design; and 4) our experimental results suggest that, interestingly, multiple voltage systems with proper voltage setup can be very close to DVS technique's full potential in energy saving.